Pond circle - Franco, Betsy; Vitale, Stefano (New York : Margaret K. McElderry Books, 2009)
In the pond by Anna's house, a food chain begins with algae which is eaten by a mayfly nymph and ends with a coyote eating a raccoon.
Kirkus Review.
School Library Journal.
3.7
K-3
Keywords: Animals -- Food -- Juvenile fiction; Ecology -- Juvenile fiction; Food chains (Ecology) -- Juvenile fiction; Pond ecology -- Juvenile fiction; Animals -- Food -- Fiction; Ecology -- Fiction; Food chains (Ecology) -- Fiction; Pond ecology -- Fiction; Animals -- Food -- Fiction; Ecology -- Fiction; Food chains (Ecology); Pond ecology -- Fiction; Picture books for children